Complete mitochondrial genome of Kashgarian loach, Triplophysayarkandensis (Day, 1877) in the Tarim river. (2nd September 2016) - Gong, Xiaoling; Xu, Huibin; Xiang, Wei; Fan, Zhengming; Zheng, Libin; Wang, Chenghui
Abstract: Kashgarian loach, Triplophysayarkandensis (Day, 1877), a native species in the Tarim River of Northwest China, has been dramatically declined in population size in recent years. In this article, the mitochondrial genome of Kashgarian loach was first determined. The whole mtDNA sequence was 16, 574 bp in length, which is similar to other bony fishes in gene order, including 2rRNA genes, 22tRNA, 13 protein-coding and 1 putative control region.